A hellion in her bed [large type] - Jeffries, Sabrina (Jeffries, Sabrina. Hellions of Halstead Hall, 2011)
Mired in scandal after his parents' mysterious deaths, notorious gambler Lord Jarret Sharpe agrees to tamely run the family brewery for a year if his Machiavellian grandmother rescinds her ultimatum that he marry. But the gambler in him can't resist when beguiling Annabel Lake proposes a wager. If she wins their card game, he must help save her family's foundering brewery. But if he wins, she must spend a night in his bed. The outcome sets off a chain of events that threatens to destroy all his plans.